KDE Programming Bible - Griffith, Arthur (IDG Books Worldwide, 2011)
Designed for beginning to advanced C and C++ programmers, this tutorial teaches readers the details of building GUI interfaces for desktop applications that will run in the KDE desktop environment. Because KDE is built on the legacy X-window graphics APIs, as well as the widgets of the widely distributed KDE Toolkit, readers must master a complex programming architecture, as well as the intricacies of standard GUI elements such as windows, events, toolbars and menus. Expert author Arthur Griffith untangles this web of relationships and shows readers how to build compelling GUIs for Linux workstations and other desktops.